2019
DOI: 10.1063/1.5123013
|View full text |Cite
|
Sign up to set email alerts
|

The static local field correction of the warm dense electron gas: An ab initio path integral Monte Carlo study and machine learning representation

Abstract: The study of matter at extreme densities and temperatures as they occur in astrophysical objects and state-of-the art experiments with high-intensity lasers is of high current interest for many applications. While no overarching theory for this regime exists, accurate data for the density response of correlated electrons to an external perturbation are of paramount importance. In this context, the key quantity is given by the local field correction (LFC), which provides a wave-vector resolved description of ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
206
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 102 publications
(226 citation statements)
references
References 128 publications
(215 reference statements)
18
206
0
Order By: Relevance
“…In the HED regime, both dielectric methods provide accurate results with a maximum deviation in χ(q) of ∼ 4% (∼ 1%) for RPA (STLS) at θ = 0.85 and r s = 0.5. In this way, we have bridged the gap between previous PIMC simulation results in the WDM regime and beyond [75,11,76] and perturbative expansions like dielectric theories [3,130,131]; iii) we have shown that our PIMC approach to the static density response converges towards RPA both for high temperatures and densities, and is in striking agreement to highly accurate CPIMC data, where they are available. This illustrates the consistency of our approach, and further corroborates our current understanding of the UEG at finite temperature.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…In the HED regime, both dielectric methods provide accurate results with a maximum deviation in χ(q) of ∼ 4% (∼ 1%) for RPA (STLS) at θ = 0.85 and r s = 0.5. In this way, we have bridged the gap between previous PIMC simulation results in the WDM regime and beyond [75,11,76] and perturbative expansions like dielectric theories [3,130,131]; iii) we have shown that our PIMC approach to the static density response converges towards RPA both for high temperatures and densities, and is in striking agreement to highly accurate CPIMC data, where they are available. This illustrates the consistency of our approach, and further corroborates our current understanding of the UEG at finite temperature.…”
Section: Discussionsupporting
confidence: 73%
“…Note that the r s = 1 results (blue diamonds) already fall into the WDM regime and have been taken from Ref. [75]. First and foremost, we note that the density response of the UEG to an external perturbation systematically increases towards small r s .…”
Section: Pimc Data For the Static Density Responsesupporting
confidence: 53%
See 3 more Smart Citations